Migration, Location and Remuneration of Medical Personnel: Physicians and Dentists - Benham, L.; Maurizi, A.; Reder, M. W. (The Review of Economics and Statistics, 1968)
OR many years there has been deep concern as to whether a shortage of doctors exists either nationally or in particular localities. This study investigates how well the distribution of the national stocks of medics (the generic term used here to refer to physicians and dentists) among areas corresponds to the distribution of population, and what influence is exerted by other variables such as effective demand for medical service, barriers to migration, and the locational preferences of medics. The unit of area in this study is the state; this is mainly because of availability of data. However, differences of size among the states, as well as in the relative populations of rural and urban areas and in the distribution of the urban population among large and small cities, seriously affect the observations. To remedy the resulting distortions as fully as possible, one of the authors is now analyzing the determinants of physician location among counties with results to be presented in a subsequent paper. However, many more variables for longer periods of time can be analyzed for states as a whole than for smaller sub-divisions.' The substance of our findings is contained in the regressions presented in the various tables. In considering them, the reader should bear in mind the following points: (1) We have analyzed a number of distinct types of medics: All Physicians, Self-employed Physicians and Dentists. Where our findings apply to all types we make generic statements. (2) To avoid discursiveness we discuss only those coefficients believed indicative of pervasive long-run forces affecting the allocation of medics. (3) In section I, the discussion is purely descriptive, i.e., the regression coefficients reflect observed associations but are not estimates of the structural parameters of a particular model. They do, however, have theoretical relevance. Some estimates of demand and supply functions are discussed in section II. (4) The years studied are 1930, 1940, 1950 and 1960 or, for some variables, years close to them. Lack of data for a sufficient number of years makes satisfactory time series analysis impossible. Section III summarizes our findings, and comments briefly upon their empirical implications. Our dictionary of variables is as follows: X (i)-Number of medics in the ith state. X2 -) Population of the ith state. X3()(Total) personal income of the ith state. X4-Volume of training facilities (number of places in medical classes) in ith state. X5-i Barriers to entry (percentage of applicants for licensure who fail examinations) in ith state. X6Population in ith state living in urban areas of more than 2,500 persons. X7-) Average income of medics in ith state.